Diseño del plan estratégico para la distribuidora monit alimentos en la ciudad de Santo Domingo de los Colorados período 2017 - 2021 - Salvatierra Cedeño, Jhonny José (2018)
This research was conducted with the purpose of designing a strategic plan that would allow improvement in the management of the Monit food distributor, 3 methodological phases in relation to the subject of study were developed for this purpose: 1) is He diagnosed the internal and external context to know the current situation of the distributor through the interview and survey tools that helped assess the environment inside and outside the enterprise by means of a questionnaire addressed to the population of Santo Sunday and to the staff of the Organization, then applied the EFI, EFE and the SWOT matrices that allowed the search and analysis of positive and negative factors that implicate in the management thereof; 2) established administrative, commercial and financial strategic objectives that would allow the strengthening of position in the market, contributing to the performance of the distributor in new revenue; (3) developed a strategic plan for Monit food distributor that enabled the creation of elements such as the mission, vision, policy and values which granted the Organization a distinctive role; very different to its competitors thus improving its image and creating strategies DO, DA, FA FO to generate new tactics that will help you to the Distributor to achieve its purpose; also was made the delivery of the strategic plan to the Manager of the distributor with the purpose that it approve the continuous development of the same.